Abrasion of 6 dentifrices measured by vertical scanning interference microscopy - Florence Pascaretti-Grizon; Guillaume Mabilleau; Daniel Chappard (University of São Paulo, 2013)
OBJECTIVES: The abrasion of dentifrices is well recognized to eliminate the dental plaque. The aims of this study were to characterize the abrasive powders of 6 dentifrices (3 toothpastes and 3 toothpowders) and to measure the abrasion on a test surface by Vertical Scanning Interference microscopy (VSI). MATERIAL AND METHODS: Bright field and polarization microscopy were used to identify the abrasive particles on the crude dentifrices and after prolonged washes. Scanning electron microscopy and microanalysis characterized the shape and nature of the particles. Standardized and polished blocks of poly(methylmethacrylate) were brushed with a commercial electric toothbrush with the dentifrices. VSI quantified the mean roughness (Ra) and illustrated in 3D the abraded areas. RESULTS: Toothpastes induced a limited abrasion. Toothpowders induced a significantly higher roughness linked to the size of the abrasive particles. One powder (Gencix® produced a high abrasion when used with a standard testing weight. However, the powder is based on pumice particles covered by a plant homogenate that readily dissolves in water. When used in the same volume, or after dispersion in water, Ra was markedly reduced. CONCLUSION: Light and electron microscopy characterize the abrasive particles and VSI is a new tool allowing the analysis of large surface of abraded materials.